Immigration of Circassians to the Ottoman Empire in the 1820s–1850s. - Georgy V. Chochiev (Кавказология, 2023)
Long before the mass exodus of the Northwestern Caucasus people representatives to the Ottoman Empire during the final stage of the Caucasian War, there were sporadic group and individual migrations of Circassians to the Sultan’s possessions, directly or indirectly caused by Russian military-political expansion in the region. These episodes of the early Caucasian muhajirism, as well as the situation of this settlers in the Ottoman possessions, usually remain outside the attention of researchers. This article, based mostly on the Turkish archival sources and testimonies of contemporaries introduced into scientific circulation for the first time, reveals the cases of immigrant communities and families from Circassia to the Ottoman territory, traces their relocations and main places of temporary and permanent settlement in Anatolia and characterizes the features of the settlers’ adaptation in their new homeland within the framework of the emerging colonization policy of the Porte during the 1820s–1850s. In this regard, this article clarifies some circumstances of the stay and activity in the Ottoman state of one of the significant figures of the Hadjret resistance in the Trans-Kuban region - Prince Hatokshoko Mohammed Asha.